L'ordre du discours - Foucault, Michel 1926-1984 (Paris Gallimard, 1971)
'L'ordre du discours' was the subject of Michel Foucault's inaugural lecture at the Collège de France, given on 2 December 1970.Foucault presents the hypothesis that in any society the production of discourse is controlled, in order to eliminate powers and dangers and contain random events in this production.
Keywords: Philosophy; Sociology; Education